Progressive Development of Creative Design Skills from Kindergarden Education - Yalcin, Meryem (FormAkademisk, 2015)
This article offers an alternative view of design education, emphasising on its introduction in kindergarten and proposing a curriculum that covers design issues for introduction in kindergarten. This approach is suited to developing creative thinking skills. In an environment where children imagine, create, practice, modify, recognise, manipulate and share knowledge, experiences and objects are crucial in design education. Early childhood education should be advanced based on basic design issues—such as design principles, conceptualization, 2D/3D spatial allocation and composition—more comprehensively, which will enable children to construct perceptual, critical and analytic view points at an early age and develop these perspectives in the future. Based on this argument, the study model for design education in kindergarten, which will instil in children strong design knowledge, as well as stimulate their cognitive development.